High‐Grade Salivary Duct Carcinoma of the Parotid Gland: Clinicopathologic Features and Treatment Outcomes. (2nd September 2014) - Mifsud, Matthew J.; Leon, Marino E.; Otto, Kristen J.; Sharma, Saurabh; Padhya, Tapan A.; Caudell, Jimmy J.
Abstract : Objectives: (1) Analyze the treatment approach for these rare salivary gland neoplasms at our institution. (2) Demonstrate observed patterns of failure and survival for high‐grade salivary duct carcinoma (HGSDC) involving the parotid glands. Methods: Clinical data on 17 patients with nonmetastatic HGSDC involving parotid salivary glands from 1998 to 2012 were abstracted from our institutional database. Inclusion required surgical resection with postoperative radiotherapy (n = 8) or concurrent chemoradiotherapy (n = 9). Demographics, histopathologic features, treatment course, and clinical outcomes were recorded. Specimens were re‐reviewed by a dedicated head and neck pathologist. Overall survival (OS) and disease‐free survival (DFS) were estimated via Kaplan‐Meier method, and comparisons were made with the log‐rank test. Results: Median patient age was 65 years (range, 52‐83 years) with a male:female ratio of 7.5:1 and median follow‐up of 37 months. Most commonly, these cases presented as pT4a (n = 14) with adverse clinical features, including perineural invasion (76.5%), positive lymph nodes (76.5%), and vascular invasion (58.8%). Three‐year DFS and OS were 35.7% and 61.4%, respectively. The pattern of treatment failure was predominately distant (n = 11) versus locoregional (n = 3). Univariate analysis of demographic, histopathologic, and treatment characteristics did not reveal a significant association with OS or DFS. Median survival after metastasis was 13 months, with only a single patient having a sustained treatment response >2 years after disease dissemination. Conclusions: In this series, we highlight the aggressive nature of high‐grade salivary duct carcinoma, which has a significant risk of distant recurrence and poor overall survival.